Conceptual design of a 5 MW OTEC power plant in the Oman Sea. Issue 2 (4th May 2017) - Hamedi, Amir-Sina; Sadeghzadeh, Sadegh
ABSTRACT: Developing ocean energy extraction, including ocean thermal energy conversion (OTEC), has been of interest to researchers for many decades. OTEC is a free fuel technology and could be used as a baseline power generation. These advantages plus the engineering challenge have resulted in researchers striving to design and construct prototype devices. Making use of worldwide experience, all sections of a conceptual design including site selection, technical specifications and cost estimation were carried out for an Iranian OTEC power plant. A 5 MW closed cycle floating plant with an annual average temperature difference of 22°C was chosen at a 33 km distance from Chabahar harbour. Deep seawater would be extracted from 1000 m depth and would result in 3.52 MW of net power. According to cost calculations, the levelised cost of electricity of the plant has been estimated to be approximately 0.117 /kWh, which is an acceptable level compared to other renewables. The conceptual OTEC design presented in this paper demonstrates a thermal potential in the Oman Sea which could assist with meeting the power demand for the southern coast of Iran.